Gram‐Scale Synthesis of Nanosized Li3HoBr6 Solid Electrolyte for All‐Solid‐State Li‐Se Battery. Issue 11 (8th October 2021) - Shi, Xiaomeng; Zeng, Zhichao; Zhang, Hongtu; Huang, Bolong; Sun, Mingzi; Wong, Hon Ho; Lu, Qiuyang; Luo, Wei; Huang, Yunhui; Du, Yaping; Yan, Chun‐Hua
Abstract: Rare earth (RE) based halide solid electrolytes (HEs) are recently considered as research hotspots in the field of all‐solid‐state batteries (ASSBs). The RE‐based HEs possess high ionic conductivity, credible deformability, and good stability, which can bring excellent electrochemical performances for ASSBs. However, the conventional synthetic methods of RE HEs are a mechanochemical process and co‐melting strategy, both approaches require expensive raw materials and sophisticated equipment. Therefore, a lot of research work is required to promote the preparation methods for these promising SSEs in ASSBs. Thus, a vacuum evaporation‐assisted synthesis method is developed for the massive synthesis of HEs. The as‐prepared Li3 HoBr6 (LHB) has a high lithium‐ion conductivity close to the mS cm −1 level and the LHB‐based Li‐Se ASSBs can be assembled by cold pressing. Theoretical calculations have revealed that the Li migrations are highly preferred in Li3 HoBr6 owing to the low energy cost and high tolerance of stable structure. The tetrahedral and octahedral pathways are responsible for Li migrations in short and long ranges, respectively. The results show that the LHB‐based Li‐Se battery has good stability and rate performance, indicating that LHB has potential application in the field of ASSBs. Abstract : A vacuum evaporation‐assisted method for massive synthesis of rare earth halide solid‐state electrolyte Li3 HoBr6, which has a high Li‐ion conductivity, wide electrochemical window, and good compatibility with anode and cathode materials, is developed. This approach also has the advantages of high efficiency, low cost, and high reliability, which realizes the all‐solid‐state Li‐Se battery assembled with Li3 HoBr6 with excellent electrochemical performance.